SISTEM ONTOLOGI E-LEARNING BERBASIS SEMANTIC WEB - Bernard Renaldy Suteja; Suryo Guritno; Retantyo Wardoyo; Ahmad Ashari (Jurnal Ilmu Komputer dan Informasi, 2009)
E-learning content being a barrier for e-learning is no longer true on todays Internet. The current concerns are how to effectively annotate and organize the available content (both textual and non-textual) to facilitate effective sharing, reusability and customization. In this paper, we explain a component-oriented approach to organize content in an ontology. We also illustrate our 3-tier e-learning content management architecture and relevant interfaces. We use a simple yet intuitive example to successfully demonstrate the current working prototype which is capable of compiling personalized course materials. The e-learning system explained here uses the said ontology.